Acute myocardial infarction due to left main coronary artery occlusion: state of the art - Rita Alexandra Mendonça Pinto Ribeiro (2021)
Acute myocardial infarction (AMI) due to left main coronary artery (LMCA) occlusion accounts for less than 1% of all primary percutaneous coronary interventions (PCI). Although rare, this critical condition frequently leads to hemodynamic instability and death. Primary PCI is the recommended treatment strategy in patients with ST-segment elevation AMI or high-risk non-ST-segment elevation AMI. Evidence concerning the optimal management of patients presenting with AMI due to acute LMCA occlusion is limited. Despite improvements in the treatment of patients with AMI, as the implementation of early reperfusion with PCI and mechanical circulatory support devices use, the mortality rate in this subgroup of patients remains high. This review summarizes the epidemiology, clinical presentation, electrocardiographic and angiographic findings, and revascularization strategies of AMI due to acute LMCA occlusion. It also helps to clarify the prognosis of these patients, identifies the gaps in the current data and outlines the need for further randomized trials to answer the remaining open questions.